Inovasi Pelayanan Publik Samsat Online Isen Mulang di Palangka Raya - Muhamad Yusuf; Denok Kuniasih (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The government has to deal with a variety of complex problems, including railroad accumulation, illegal fishing, brokerage activities, and even the general public's lack of awareness and willingness to pay motor vehicle taxes. The purpose of this study is to provide a comprehensive description of the E-Samsat service innovation, which is a public service innovation. The research method used in this research is this type of research using literature study research techniques. Since information relevant to the topic or problem being studied is collected by the researcher during the data collection process, this information can be obtained in research reports, journals, scientific papers, theses and dissertations, regulations, encyclopedias, and written sources that are both printed and in data form. electronic. The findings from this study indicate that e-Samsat service innovation has many aspects. Where is the Relative Advantage, namely the ease of the community in managing motorized vehicle tax payments (PKB). Compatibility (suitability) where e-samsat service innovations for the community are in accordance with the current conditions of technological development. Complexity (complexity) where e-samsat service innovation is felt to be uncomplicated in the implementation process. Then Triability (possibility of trying) people who respond positively to the e-samsat service. Furthermore, from Observability (ease of being observed) with a fairly simple service procedure electronically.